Preparation and characterization of hydrophobic silica zirconium nanoparticles - Ellateif, T.M.A. (Trans Tech Publications Ltd, 2014)
Hydrophobic silica nanoparticles were synthesized by silica sols modified with different percentage of zirconium sol using liquid modification. The hydrophobicity test demonstrated that silica zirconium nanoparticles are more hydrophobic as they showed 1 to 5 weight gain compared to 8 for pure silica nanoparticles. The synthesized silica nanoparticles were characterized using different techniques to investigate the effect of zirconium modification on silica nanoparticles characteristics. Structure and composition of unmodified silica nanoparticles and modified one were studied using FTIR; the results showed that the zirconium oxide was anchored to the surface of silica nanoparticles. TEM and BET analysis showed that the percentage of zirconium added to silica had distinct effect on the particle distribution and surface area of silica nanoparticles. Â© 2014 Trans Tech Publications, Switzerland.